Analgesic efficacy of two concentrations of bupivacaine in women in labor: Randomized, controlled, triple blind clinical trial☆. Issue 3 (2015) - Rodríguez‐Ramón, Ricardo; Márquez‐González, Horacio; Jiménez‐Báez, María Valeria; Iparrea‐Ramos, Ilse Cristina
ABSTRACT : Introduction: : Epidural analgesia is the safest and most effective method for the treatment of pain during childbirth. Epidural bupivacaine provides excellent analgesia for labor and remains the most widely used local anesthetic in obstetric anesthesia. Objective: : To evaluate the analgesic efficacy of two concentrations of bupivacaine in women in labor. Methods: : 114 patients in labor with term pregnancy were included in the study. They were grouped randomly into two groups: patients who received bupivacaine at 0.125% (group A) and those who received 0.25% bupivacaine (group B). Patients in group A received a bolus injection of 10 ml of 0.125% bupivacaine. The patients in group B received a bolus of 10 ml bupivacaine 0.25%. Pain intensity according to VAS, blood pressure, heart rate, respiratory rate, and the degree of motor block was assessed using the Bromage scale at different periods of time. Results: : Demographic characteristics and parity were compared with no statistically significant differences found. By comparing the values of the VAS measure at 0, 15, 30, 60 and 90 min, statistically significant differences in favor of the group with 0.25% bupivacaine were found with decreased pain perception after 30 min, p ‐value = 0.02. No differences in arterial pressure, heart rate and respiratory rate were found between the two groups. Conclusion: : The concentration of 0.25% bupivacaine has greater analgesic efficacy compared to 0.125% bupivacaine. RESUMEN : Introducción: : La analgesia epidural es el método más seguro y eficaz para el tratamiento del dolor del parto. La Bupivacaína epidural proporciona una analgesia excelente para el parto y sigue siendo el anestésico local más utilizado en anestesia obstétrica. Objetivo: : Evaluar la eficacia analgésica entre dos concentraciones de Bupivacaína en mujeres en trabajo de parto. Métodos: : Se incluyeron 114 pacientes en trabajo de parto con embarazo de término. Se agruparon de forma aleatoria en dos grupos; pacientes que recibieron Bupivacaína al 0, 125% (grupo A) y Bupivacaína al 0, 25% (grupo B). Las pacientes del grupo A recibieron 10 ml de Bupivacaína al 0, 125% en bolo. Las pacientes del grupo B recibieron 10 ml. de Bupivacaína al 0, 25% en bolo. Se valoró la intensidad del dolor según la EVA, la presión arterial, frecuencia cardiaca, frecuencia respiratoria, el grado de bloqueo motor según la escala de Bromage en diferentes periodos de tiempo. Resultados: : Las características demográficas y de paridad se compararon, sin encontrar diferencias estadísticamente significativas. Al comparar los valores de la EVA medida en el minuto 0, 15, 30, 60 y 90 se encontraron diferencias estadísticamente significativas a favor del grupo con Bupivacaína al 0, 25% con disminución de la percepción del dolor a partir del minuto 30, valor de p de 0, 02. No se encontraron diferencias en la Presión Arterial, frecuencia cardiaca y frecuencia respiratoria entre ambos grupos. Conclusión: : La concentración de Bupivacaína al 0, 25% mejora la eficacia analgésica en comparación con Bupivacaína al 0, 125% en mujeres con trabajo de parto activo en 6 puntos a los a partir de los 60 minutos.